Energy Prices and the Nigerian Stock Market - Alio, Felix Chukwubuzo; Okolo, Victor O.; Egbo, Obiamaka P.; Ezeaku, Hillary Chijindu (International Journal of Energy Economics and Policy, 2019)
This paper analysed the relation between the stock market indices and the developments in the international energy market using historical monthly data from January 1985 to December 2017. Energy prices as applied in the study are composed of changes in the prices of crude oil, natural gas and liquefied natural gas. We employed the traditional VAR techniques in estimating the linkages between the variables of interest. Our findings showed that changes in energy prices did not have significant influence on the stock market. Although there was evidence of a long-run relationship between the two variables, no causal relationship was found to exist between them; this entails that past values of the prices of crude oil, natural gas and liquefied natural gas were not vital in predicting the developments in the stock market. Likewise, lagged values of the stock market indices were not instrumental in forecasting the movements in energy prices. Thus, we conclude that the stock market could be more responsiveness to other macroeconomic indicators other than the energy prices. Keywords: Energy price, stock market, Granger Causality, Vector Autoregressive, Nigeria JEL Classifications: C25, Q47, F4 DOI: https://doi.org/10.32479/ijeep.7803